Measurement of the CP-violating phase ϕs and the B0s meson decay width difference with B0s→ J/ψϕ decays in ATLAS - Alconada Verzini, María Josefina (2016)
A measurement of the B0s decay parameters in the B0s→ J/ψϕ channel using an integrated luminosity of 14.3 fb-1 collected by the ATLAS detector from 8 TeV pp collisions at the LHC is presented. The measured parameters include the CP-violating phase ϕs, the decay width Γs and the width difference between the mass eigenstates ΔΓs. The values measured for the physical parameters are statistically combined with those from 4.9 fb-1 of 7 TeV data, leading to the following: Φs = -0.090 ± 0.078 (stat.) ± (syst.) rad ΔΓs = 0.085 ± 0.011 (stat.) ± 0.007 (syst.) ps-1 Γs = 0.675 ± 0.003 (stat.) ± 0.03 (syst.) ps-1 In the analysis the parameter ΔΓs is constrained to be positive. Results for ϕs and ΔΓs are also presented as 68% and 95% likelihood contours in the ϕs-ΔΓs plane. Also measured in this decay channel are the transversity amplitudes and corresponding strong phases. All measurements are in agreement with the Standard Model predictions.